1968
DOI: 10.1111/j.1570-7458.1968.tb00069.x
|View full text |Cite
|
Sign up to set email alerts
|

Contrary Responses of Musca Domestica Concerning Their Selection of Different Shades and Hues

Abstract: The results of experiments in the open air with houseflies settling on surfaces (cardboards) of light and dark shades and of various colours differed from those in laboratory tests. Whereas black is preferred to gray and to white and to all hues in the indoor tests, the white cardboards we used attracted in most cases a preponderant majority of flies in the open air but not so when placed versus yellow. It is assumed that the attraction of the white cardboard is due to the reflection of the “near ultraviolet” … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
1

Year Published

1969
1969
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 6 publications
3
10
1
Order By: Relevance
“…This contradicts previous experiments where more house ßies landed on yellow paper than on papers of other colors (Awati and Swaminath 1920), being caught in yellow painted plastic jug traps (Burg and Axtell 1984), or being attracted to yellow cards (Nava 1967, Hecht et al 1968). Wavelengths reßected by the traps used in those experiments were not reported by the authors.…”
Section: Table 2 Mean Depolarization (؎Se) In the Equatorial Region contrasting
confidence: 80%
“…This contradicts previous experiments where more house ßies landed on yellow paper than on papers of other colors (Awati and Swaminath 1920), being caught in yellow painted plastic jug traps (Burg and Axtell 1984), or being attracted to yellow cards (Nava 1967, Hecht et al 1968). Wavelengths reßected by the traps used in those experiments were not reported by the authors.…”
Section: Table 2 Mean Depolarization (؎Se) In the Equatorial Region contrasting
confidence: 80%
“…The rank order of colour preferences obtained in the present experiments resembles that of experiments in the open air byHecht et al (1968).…”
supporting
confidence: 70%
“…Spontaneous colour prelerences may be Y>B, W_>O, R> G, while the order rank of the subjective brightness to the fly is W > Y > G > B > O > R. Thus, the spontaneous colour preferences of the fly on the test array do not simply depend on subjective brightness. Hecht et al (1968) Blue and yellow are the colours the flies learn easily, and they can discriminate well between them (Figs. 5 and 9).…”
Section: Discussionmentioning
confidence: 99%
“…The responses of M. domestica to colour in the laboratory have been well documented, and Hecht (1970) concluded that contrast with the surroundings is more important than colour. In the uniform grey environment of a dairy barn it was demonstrated that the most attractive colour was yellow in the absence of any chemical stimuli ( Hecht et al . 1968 ).…”
Section: Discussionmentioning
confidence: 99%